2022
DOI: 10.1021/acs.nanolett.1c04754
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling Cathodoluminescence Spectra in Nanophotonics: Particle Eigenmodes vs Transition Radiation

Abstract: Cathodoluminescence spectroscopy performed in an electron microscope has proven a versatile tool for analyzing the near- and far-field optical response of plasmonic and dielectric nanostructures. Nevertheless, the transition radiation produced by electron impact is often disregarded in the interpretation of the spectra recorded from resonant nanoparticles. Here we show, experimentally and theoretically, that transition radiation can by itself generate distinct resonances that, depending on the time-of-flight o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 74 publications
0
4
0
Order By: Relevance
“…According to a recent study, however, transition radiation may cause distortions in recorded CL spectra in specific situations. 144 As electron beams penetrate nanoparticles, two transition radiation dipoles are formed with a temporal delay on two opposed interfaces (Figure 6a). Interference between the two dipoles can generate distinctive resonances and lead to the potentially erroneous assignment of modal characters to the spectral features.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to a recent study, however, transition radiation may cause distortions in recorded CL spectra in specific situations. 144 As electron beams penetrate nanoparticles, two transition radiation dipoles are formed with a temporal delay on two opposed interfaces (Figure 6a). Interference between the two dipoles can generate distinctive resonances and lead to the potentially erroneous assignment of modal characters to the spectral features.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of CL spectroscopy, transition radiation generated by electron impact in CL measurements is disregarded in the interpretation of the spectra from resonant nanostructures due to its weak oscillator strength compared with other resonances. According to a recent study, however, transition radiation may cause distortions in recorded CL spectra in specific situations . As electron beams penetrate nanoparticles, two transition radiation dipoles are formed with a temporal delay on two opposed interfaces (Figure a).…”
Section: Conclusion and Outlookmentioning
confidence: 99%
See 1 more Smart Citation
“…18,19,98,152 Methods were also proposed to disentangle several types of emission from farfield measurements. 202 Inspired by the early days of radio, it has been shown that a nanoscopic dipole Herzian antenna acts as an efficient emitter of visible light when an electron beam is injected in the dipole gap. 187 Thermal measurements can also be performed with CL, such as nanoscale thermometry and thermal transport measurements both in low current conditions (where sample heating is avoided) and higher current conditions 203 (where electron beam induced heating is present).…”
Section: Cathodoluminescence Spectroscopy and Polarimetry Techniquesmentioning
confidence: 99%